The Governance of Zakat Institutions: A Meta-Narrative Review - Ahmad Baehaqi; Anis Chariri; Tri Jatmiko Wahyu Prabowo (Universitas Muhammadiyah Malang, 2025)
Purpose: This study examines the evolution of zakat governance research, focusing on theoretical frameworks, methodologies, and contextual settings. Methodology/approach: A meta-narrative review guided by the RAMESES protocol is conducted using Scopus-indexed articles. Findings: Analyzing 23 Scopus-indexed articles, the study reveals significant research growth since 2011, particularly in Muslim-majority countries like Indonesia and Malaysia. However, critical gaps persist, including limited exploration of governance mechanisms such as digital technology integration, shariah audit, and risk management systems. Additionally, research remains reliant on quantitative methods and narrow theoretical perspectives. Practical implications: The findings offer actionable recommendations for improving zakat institutions' performance and fostering public trust, making this research a crucial reference for scholars, policymakers, and practitioners in Islamic social finance. Originality/value: To the best of our knowledge, this is the first study to review the governance of zakat institutions using a meta-narrative approach guided by RAMESES standards. This study provides a holistic synthesis of theoretical, conceptual, and methodological perspectives, employing relevant keywords and reputable databases.